Government appointments, patronage and social justice in South Africa - Safodien, Khalid (My University, 2016)
In this research, I‟m interested in exploring the question as to whether government appointments on the basis of patronage undermine the delivery of social goods and service and the obligations of and social justice in South Africa. One of the norms of social justice relates to the distribution of goods and services in ways that are just. As Rawls shows in A Theory of Justice, justice is not only the first virtue of society, it is one that should be thought of in terms of fairness — where fairness has to do with skewing society or the principles that govern society in ways that are responsive to the interest and good of all (rather than that of an individual or a select few or particular group). One conclusion that can be drawn from this is that to meet this requirement it is imperative that social institutions are calibrated to be sensitive to justice and with regard to appointments to government positions such appointments are done on the basis of ability to meet such obligation. As part of investigating the above question, I will discuss a number of examples that highlight that certain government appointments in South Africa are done on the basis of party affiliation and not based on skills and qualifications. As such, the most qualified people do not often hold those positions. One consequence of this is the inadequacies and inefficiencies in the distribution of social goods and services that has gradually become the norm in South Africa.
Keywords: African National Congress; Political parties--South Africa; Social justice--South Africa; South Africa--Politics and government